Orthodox Participation in the Universal Christian Conference on Life and Work, Stockholm, 1925 - Vasilevich, Natallia (The ecumenical review, 2024)
This article examines the participation of Orthodox representatives in the Universal Christian Conference on Life and Work held in Stockholm in 1925. It highlights the contributions of Orthodox hierarchs and theologians to key themes such as social ethics, international relations, and cooperative efforts among Christian communions. Despite their active involvement, the Orthodox presence at the conference has so far been underresearched. The article emphasizes the significance of the Orthodox Church, particularly the Patriarchate of Constantinople, in shaping the conference's agenda and fostering ecumenical dialogue. It also discusses the urgent call for Christian unity in addressing contemporary societal challenges and underlines the importance of Orthodox participation in advancing the goals of the ecumenical movement during a critical period in world history.